1991
DOI: 10.1115/1.2906286
|View full text |Cite
|
Sign up to set email alerts
|

Design of Ceramic Gas Turbine Components

Abstract: At the Institute for Thermal Turbomachinery (ITS), University of Karlsruhe, detailed theoretical and experimental studies concerning ceramic gas turbine components have been performed. For the analysis of the reliability of ceramic components by finite element calculations, the numerical code CERITS has been developed, which follows a strategy similar to that suggested by Gyekenyesi. CERITS determines the failure probability of ceramic components with reference to volumetric flaws. Different fracture criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a ¢rst set of experiments it was shown that membrane fragments which adsorbed to the quartz or electrode surface from standard bu¡er (containing 640 nM RH421) produce the same characteristic £uorescence changes upon substrate-induced partial reactions in the TIRF measurements as have been observed in non-TIRF £uorescence experiments with membrane fragments £oating freely in bu¡er [9,10,12]. In principle the same £uorescence behavior was found, although the amplitudes of the £uorescence changes showed some (minor) deviations.…”
Section: Fluorescence Measurementsmentioning
confidence: 69%
See 1 more Smart Citation
“…In a ¢rst set of experiments it was shown that membrane fragments which adsorbed to the quartz or electrode surface from standard bu¡er (containing 640 nM RH421) produce the same characteristic £uorescence changes upon substrate-induced partial reactions in the TIRF measurements as have been observed in non-TIRF £uorescence experiments with membrane fragments £oating freely in bu¡er [9,10,12]. In principle the same £uorescence behavior was found, although the amplitudes of the £uorescence changes showed some (minor) deviations.…”
Section: Fluorescence Measurementsmentioning
confidence: 69%
“…To understand the molecular mechanisms of transport it is of great interest to identify and to analyze how much charge is moved through the protein in each of the reaction steps [1]. Various techniques are applied to investigate the electrogenicity of Na transport: voltage jump experiments with giant patch or whole cell patch of myocardial cells [4,5], charge pulse experiments on membrane fragments adsorbed to planar lipid bilayers [6,7] or, very recently, adsorbed to solid supported bilayers [8], and a £uorescence technique applying an electrochromic styryl dye, RH421, which detects charge movements within the membrane dielectric [9,10]. The latter method provides indirect access to the so-called electrogenicity as discussed elsewhere [1,6,10].…”
Section: Introductionmentioning
confidence: 99%